Pengaruh Model Pembelajaran Problem Based Learning Berorientasi Chemoenterpreneurship Terhadap Hasil Belajar Kimia Siswa - Erma Listari (Universitas Pendidikan Mandalika Mataram, 2013)
The Effect of Problem Based Learning Model Orientation Chemo Entrepreneurship toward Students Chemistry Learning Result. (Supervised by Suryati and Devi Qurniati) This research is quasi experimental research. The population of this research is consisting of two classes with 65 students. The technic of collecting data is nonprobability sampling. The gambling technic is used to decide the experimental class and control class. By using gambling technic are decided XI IPA 1 as control class using conventional approach and XI IPA 2 as experimental class using PBL model orientation CEP. From instruments 25 test items is valid with reliability result is 0,887. The result of the study is (1) the learning process in class using PBL orientation CEP and conventional approach are going well. That is based on the average result of experimental class is 74% and the average result of control class is 71, 35%. (2) The application of PBL orientation CEP in colloid system has good effect toward student learning result. That is based on t-count 2,593 > t-table 1, 669 with average cognitive result of experimental class is 76,95 and control class is 69,33. While for affective experimental class is 74,59 and control class 67,29.